2020
DOI: 10.1002/jimd.12288
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the neurological phenotype in children with defects in the ECHS1 or HIBCH gene

Abstract: The neurological phenotype of 3-hydroxyisobutyryl-CoA hydrolase (HIBCH) and short-chain enoyl-CoA hydratase (SCEH) defects is expanding and natural history studies are necessary to improve clinical management. From 42 patients with Leigh syndrome studied by massive parallel sequencing, we identified five patients with SCEH and HIBCH deficiency. Fourteen additional patients were recruited through collaborations with other centres. In total, we analysed the neurological features and mutation spectrum in 19 new S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 57 publications
1
14
1
Order By: Relevance
“…We found 36 variants: 25 were reported as pathogenic or likely pathogenic, and 11 were novel (pathogenic n =5, likely pathogenic n =5, variant of unknown significance n =1). In six out of 11 novel variants, functional studies and biomarker analysis had previously demonstrated their contribution to the phenotype 5,10–14 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found 36 variants: 25 were reported as pathogenic or likely pathogenic, and 11 were novel (pathogenic n =5, likely pathogenic n =5, variant of unknown significance n =1). In six out of 11 novel variants, functional studies and biomarker analysis had previously demonstrated their contribution to the phenotype 5,10–14 …”
Section: Resultsmentioning
confidence: 99%
“…Methylmalonic aciduria was observed in a patient with SUCLG‐ related Leigh syndrome. Patients with HIBCH defects showed high levels of 3‐hydroxyisobutyryl carnitine or 3‐hydroxyisovaleric acid 10 (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The phenotypic spectrum of the disease range from neonatal-onset severe phenotype with myriad of neurological and multisystem manifestations 7 to milder phenotypes presenting at >2 years with paroxysmal and exercise induced dyskinesias triggered by increased energy demand. 8,9 However, multiple types of persistent hyperkinetic movement disorders 10 have not yet been described. Phenotypic heterogeneity exists for the same genotype, often making the diagnosis challenging.…”
Section: Introductionmentioning
confidence: 99%